New campus-Agricultural Science building-0001
Modern Facilities for the trainning of the future farm leaders are housed in an agriculture located in the 160-acre academic center. The two-story structure, built at a cost of $ 775,000, houses 11 up-todate labboratories for experimentation in farm subjects, as well as classrooms and administrative offices. The open-winged agriculture unit has become a popular meeting place for majors who gather to discuss classroom and extra-curricular matters.